Blended Learning in Package C Equality Programs in Facing New Normal Education - Yeni Rita; Nadia Safitri (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2020)
The background of this research is the occurrence a big disaster in this era that hit all of the worlds and makes an impact in various shock and various sector, including the education sectors. The package C program also experienced the impact of this pandemic by not allowing face to face and closely, so the citizens learn difficulties in learning. The purpose of this research is to offer an option in the form of a learning model for Package C learning citizens, namely blended learning. On the other hand, the purpose of this research also to show the benefits of blended learning to package C program to faced new normal education. The result of this research is showing to effectively blended learning applied to the package C program, especially during this pandemic. The benefits obtained by the citizens of learning in blended learning are: (1) citizens learn are more used to technology in learning; (2) to reduce the dependence on the presence of tutor in learning face to face learning; and (3) allow them the opportunity to go into online business. The researcher hoped that blended learning will be further encouraged till citizens learn to be more independent in learning and tutors or are expected to be able to adjust to the new normal education. Keywords: blended learning, package C, New normal education.